KONSEP PENCATATAN HUTANG PIUTANG DALAM AL-QUR’AN (Tinjauan Tafsir Kabir Mafatikhul Ghaib Karya Imam Fahrurrazi) - Fahruddin, Achmad (Ekonomi Syariah STAI Sangatta Kutai Timur, 2020)
Guidance from God to humans in living life in order to be safe in this world and the hereafter is implemented in the form of sharia. The purpose of the implementation of the Shari'a is for the benefit of humans in order to provide benefits and also so that humans avoid damage (mafsadah) in the world and the hereafter. The shari'a that Allah has given to humans is in the form of sharia in worship and also muamalah. Sharia in muamalah, among others, is in the form of sharia in buying and selling, leasing, accounts payable and others. In the debt law, which in Arabic is called dain, it is contained in Q.S. Al-Baqarah (2) verses 280, 282 and 283. Verses 282-283, which is the longest verse in the Al-Qur'an, contain the concept or procedure for recording accounts payable. In this paragraph there is a sentence amr or an order to record accounts payable in any non-cash transaction, whether it is a non-existent transaction or a transaction of large value. The sentence amr in this verse is interpreted differently by the commentators. There are commentators who state that the sentence amr in the verse indicates an obligatory commandment. However, according to the mufufasir, it states that the amr in the verse shows a mandatory meaning, but only shows the meaning of circumcision or recommendation, which is written in the book by Imam Fahrurrazi, namely Tafsir Kabir Mafatikhul Ghaib.